Sequential algorithm of parabolic equation in solving thermal control process on printed circuit board - Norma Alias, author; Fatimah Sham Ismail, 1966-, author; Ali Hassan Mohamed Murid, author; Zarith Safiza Abdul Ghaffar, author; Hazrina Hassan, author; Regional Annual Fundamental Science Seminar (2008 : Johor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL